A Comparative Study of Modern and Heirloom Wheat on Markers of Gastrointestinal Health (FS12-03-19) - Keirns, Bryant (Curr Dev Nutr, 2019)
OBJECTIVES: Wheat consumption has declined the past two decades amid growing concerns about gluten-sensitivity. To determine if genetic manipulations of wheat contribute to gut inflammation, we investigated the effects of modern and heirloom wheat on gut health under normal and western diet (WD) conditions. METHODS: Six-week old C57BL/6 male mice were utilized in a 2 × 3 factorial design with diet (control [AIN-93 G] or WD, 45% fat) and wheat flour (control, 10% heirloom [Turkey] or modern [Gallagher]) as factors. After 6 wks on diets, body composition was assessed, and blood and tissue specimens were collected to evaluate metabolic parameters, as well as systemic and intestinal indicators of inflammation and barrier integrity. Cecal short-chain fatty acids (SCFAs) were also assessed. Data were analyzed using 2-way ANOVA (SAS, Version 9.4) unless tests of normality failed, in which case Friedman's test was performed. RESULTS: Body weight, % body fat, fasting glucose, total cholesterol, and NEFA were increased with WD and wheat had no effect on these metabolic parameters. Serum C reactive protein and lipopolysaccharide binding protein were not changed by WD or wheat. WD decreased the SCFA, acetic acid, but adding Gallagher wheat to WD restored levels to control (P(WD*Wheat )< 0.05). No other SCFA were altered. Histological evaluation revealed reduced villi height (P < 0.05) and area (P < 0.05) in the jejunum with WD and wheat did not alter this response. Within the ileum, Gallagher increased villi area (P < 0.01) relative to control, but no other changes were noted. No effects of WD or wheat on villous atrophy or lymphocyte infiltration within the jejunum, ileum or colon were observed. Overall, gene expression of tight junction proteins was unaffected by WD or wheat, except for a reduction in junction adhesion molecule-3 (Jam3) by WD (P < 0.05). Within the ilial lamina propria, WD increased interferon-γ (IFNg) (P < 0.05) and adding Turkey wheat suppressed interleukin-17 (IL17) (P(WD*Wheat )< 0.05) relative to other groups. No other inflammatory cytokines (tumor necrosis factor-α [Tnf], IFNg, and Il6) were altered by wheat. CONCLUSIONS: These findings indicate modern wheat (Gallagher) did not comprise barrier function or contribute to gut inflammation relative to the Turkey variety. FUNDING SOURCES: Oklahoma Wheat Commission.